Evaluasi Strategi Creating Shared Value (CSV) Kedepan Yang Bernilai Sustainable Development Goals (SDG) Pada PT Kawasan Industri Gresik - Ni’mah, Magfirotun (Rifa'Institute, 2022)
Following the times, the paradigm of realizing social and environmental responsibility will inevitably have an impact on the company in the future. Therefore, companies need to make efforts to integrate economic interests and fulfill social and environmental responsibilities. SDGs have become a measuring tool in determining Impact Ranking. Academics are stakeholders who play a role in helping the achievement of the SDGs. This study aims to identify the level of effectiveness of the strategies that have been carried out and the role of the Sustainable Development Goals (SDG) Creating Shared Value (CSV) Strategy at PT Kawasan Industri Gresik. This study uses a qualitative method regarding the Evaluation of the Strategy of Creating Shared Value (CSV) in the future which is worth the Sustainable Development Goals (SDG). The results of this study are CSR activities of PT Kawasan Industri Gresik which have the most significant impact are Orphans Compensation with the highest SROI output value of 5. The allocation and positive impact caused by the company has not been balanced between social and environmental. PT Kawasan Industri Gresik allocates more funds for social activities for communities around the affected areas. Although the impact is quite good, the overall ratio of positive environmental impacts is very small compared to the social impact of the CSR programs that have been carried out. Through this CSR effectiveness evaluation study, it can be seen the impact of PT Kawasan Industri Gresik's CSR program in detail in rupiah nominal terms